Genetic Ablation of G Protein-Gated Inwardly Rectifying K+ Channels Prevents Training-Induced Sinus Bradycardia - Bidaud, Isabelle; D’Souza, Alicia; Forte, Gabriella; Torre, Eleonora; Greuet, Denis; Thirard, Steeve; Anderson, Cali; Chung You Chong, Antony; Torrente, Angelo G.; Roussel, Julien; Wickman, Kevin; Boyett, Mark R.; et al. (Frontiers in Physiology, 2021)
Background: Endurance athletes are prone to bradyarrhythmias, which in the long-term may underscore the increased incidence of pacemaker implantation reported in this population. Our previous work in rodent models has shown training-induced sinus bradycardia to be due to microRNA (miR)-mediated transcriptional remodeling of the HCN4 channel, leading to a reduction of the “funny” (If) current in the sinoatrial node (SAN). Objective: To test if genetic ablation of G-protein-gated inwardly rectifying potassium channel, also known as IKACh channels prevents sinus bradycardia induced by intensive exercise training in mice. Methods: Control wild-type (WT) and mice lacking GIRK4 (Girk4–/–), an integral subunit of IKACh were assigned to trained or sedentary groups. Mice in the trained group underwent 1-h exercise swimming twice a day for 28 days, 7 days per week. We performed electrocardiogram recordings and echocardiography in both groups at baseline, during and after the training period. At training cessation, mice were euthanized and SAN tissues were isolated for patch clamp recordings in isolated SAN cells and molecular profiling by quantitative PCR (qPCR) and western blotting. Results: At swimming cessation trained WT mice presented with a significantly lower resting HR that was reversible by acute IKACh block whereas Girk4–/– mice failed to develop a training-induced sinus bradycardia. In line with HR reduction, action potential rate, density of If, as well as of T- and L-type Ca2+ currents (ICaT and ICaL) were significantly reduced only in SAN cells obtained from WT-trained mice. If reduction in WT mice was concomitant with downregulation of HCN4 transcript and protein, attributable to increased expression of corresponding repressor microRNAs (miRs) whereas reduced ICaL in WT mice was associated with reduced Cav1.3 protein levels. Strikingly, IKACh ablation suppressed all training-induced molecular remodeling observed in WT mice. Conclusion: Genetic ablation of cardiac IKACh in mice prevents exercise-induced sinus bradycardia by suppressing training induced remodeling of inward currents If, ICaT and ICaL due in part to the prevention of miR-mediated transcriptional remodeling of HCN4 and likely post transcriptional remodeling of Cav1.3. Strategies targeting cardiac IKACh may therefore represent an alternative to pacemaker implantation for bradyarrhythmias seen in some veteran athletes.